Deep traps can reduce memory effects of shallower ones in scintillators. Issue 2 (14th December 2015) - Moretti, Federico; Patton, Gaël; Belsky, Andrei; Petrosyan, Ashot G.; Dujardin, Christophe
Abstract : We propose a new strategy to reduce the X-ray induced luminescence sensitization in scintillators by the addition of suitably designed high concentration deep traps for free charge carriers. Abstract : X-ray induced luminescence sensitization results have been obtained on three commercially relevant scintillators, namely CsI:Tl, YAG:Ce and LSO:Ce. The obtained curves have been used to validate a model based on the competition among trapping and recombination of free charge carriers. The model was able to accurately describe the complex phenomenology of the detected sensitization curves. We also used the model to predict the role of a high temperature and concentration trap in shaping the sensitization curves. Based on these modelling results we also proposed a novel, and rather counterintuitive, strategy to deal with the sensitization phenomenon based on the deliberate introduction of deep traps which can significantly reduce the bright burn effect.